PENERAPAN KONSEP TRI HITA KARANA DALAM PERENCANAAN PERUMAHAN DI BALI - Wastika, Dewa Nyoman (Jurnal Natah; Vol. 3, No. 2 Agustus 2005)
Tri Hita Karana is as a concept which be apparently used on Balinese traditional housing. Balinese traditional house incorporate strongly on the use of environment such as non biotical, biotical and socio culture as well. In developing the Balinese traditional housing, it utilizes optimally the local environment in order that it is able to attain the situation and condition which is a very comfortable, efficiently energy and cheaply use as well. Through the development of science and technology, the rise of tourism influence and the growth of population as well, the concept of Tri Hita Karana is steadily abandoned even forgotten and altered by other concept which is actually come from outside of Bali and in fact, we recognize that it is not guarantee to be applicable in Bali. It is not painless to defeat those change in Bali. It seems that we require durably a strategy manner to optimize the positive influence that come from out of Bali to be able to develop more efficient and effective. The other hand, the negative influence will be minimized, even eliminated through such great efforts to employ optimally the concepts that is still taking place nowadays in Bali. Hopefully, throughout the implementation of Tri Hita Karana, the development of Balinese traditional housing can be sustainable.
Keywords: science, technology, Tri Hita Karana and housing planning